Approach to Pediatric Emergency - Jaydeep Choudhury (Jaypee Brothers Medical Publishers, 2011)
Approach to Pediatric Emergency is practical approach-based, algorithmic and naturally ready to use. This "at a glance" format can be accessed by emergency physicians, emergency fellows, trainees, pediatric postgraduates and even practicing pediatricians.